Differential Regulation of Slc40a1, Fth1, and Hmox1 by Deferasirox in Splenic Iron Overload - Wibowo, Annisa Maharani; Kuntana, Yasmi Purnamasari; Arrizqiani, Tanendri; Safitri, Ratu (Sciences of Pharmacy, 2025)
Iron overload, often arising from repeated transfusions in thalassemia major, disrupts iron homeostasis and induces oxidative stress. Deferasirox is a widely used oral chelator, yet its effects on splenic iron-regulatory gene expression remain unclear. This study investigated the impact of deferasirox on ferritin heavy chain (Fth1), ferroportin (Slc40a1), and heme oxygenase-1 (Hmox1) expression in a rat model of splenic iron overload. Eighteen male Wistar rats were randomly assigned into three groups (n = 6 each): normal (N), iron dextran-induced overload without treatment (KN), and iron overload treated with deferasirox (KP). Gene expression was quantified by real-time PCR using the 2−ΔΔCT (Livak) method, with statistical analysis performed via one-way ANOVA and Tukey’s post hoc test. Iron overload significantly upregulated Fth1 (2.26-fold) and Slc40a1 (1.72-fold) versus controls (p < 0.05). Deferasirox treatment reduced Fth1 (3.28-fold decrease) and Slc40a1 (1.15-fold reduction) relative to untreated overload, though not significantly (p > 0.05). In contrast, Hmox1 expression markedly increased (55.25-fold, p < 0.05) following deferasirox administration. These results indicate that deferasirox selectively modulates splenic iron-regulatory genes, suggesting both chelation and adaptive stress-response mechanisms, thereby supporting its therapeutic role in managing iron overload.